2000
DOI: 10.1046/j.1460-9568.2000.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the human frontal eye field and multiple parietal areas in covert visual selection during conjunction search

Abstract: Searching for a target object in a cluttered visual scene requires active visual attention if the target differs from distractors not by elementary visual features but rather by a feature conjunction. We used functional magnetic resonance imaging (fMRI) in human subjects to investigate the functional neuroanatomy of attentional mechanisms employed during conjunction search. In the experimental condition, subjects searched for a target defined by a conjunction of colour and orientation. In the baseline conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 46 publications
11
94
0
1
Order By: Relevance
“…This study was approved by the Human Investigations Committee of the Yale University School of Medicine. Ten subjects (six males, four females, ages 21-36) participated in the first experiment whereas two other groups of 15 subjects participated in the second experiment (eight males, ages [19][20][21][22][23][24][25][26][27][28][29][30] and control experiment (six males, ages 20-37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the Human Investigations Committee of the Yale University School of Medicine. Ten subjects (six males, four females, ages 21-36) participated in the first experiment whereas two other groups of 15 subjects participated in the second experiment (eight males, ages [19][20][21][22][23][24][25][26][27][28][29][30] and control experiment (six males, ages 20-37).…”
Section: Methodsmentioning
confidence: 99%
“…Although some neuropsychological studies support the hypothesis that the parietal cortex is involved in feature integration (11)(12)(13), others do not (14). In addition, previous functional imaging studies have either shown no evidence for parietal cortex involvement in feature conjunction (15)(16)(17) or have produced inconclusive evidence (18)(19)(20) because of potential confounds such as task difficulty and͞or eye movements (19,21).…”
mentioning
confidence: 99%
“…Neuroimaging studies have consistently revealed both rPPC and rFEF to be involved in visual search (Donner et al, 2000;2002;Nobre et al, 2003) and transcranial magnetic stimulation (TMS) has demonstrated the importance of both areas in the control of conjunction search (Ellison et al, 2003;Lane et al, 2011a;Muggleton et al, 2003. However, to date this has only been investigated for near space, typically with the search arrays presented on a computer monitor.…”
Section: Introductionmentioning
confidence: 99%
“…2000;Beauchamp & al. 2001], by visual conjunction search [Donner & al. 2000], and by covert attentive tracking of moving targets [Culham & al.…”
Section: Discussionmentioning
confidence: 99%